2023
DOI: 10.5194/egusphere-egu23-12618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fusion of Sentinel-1 and Sentinel-2 satellite imagery to rapidly detect landslides through Google Earth Engine

Abstract: <div> <p><span data-contrast="auto">Landslides constitute a significant geohazard causing human losses and significantly affecting the economy worldwide. Earth Observation and the exploitation of the freely available Copernicus datasets, such as the Sentinel-1 and Sentinel-2 satellite images, can assist in the systematic monitoring of landslides overcoming the restrictions arising from in situ measurements. This study shows how the Google Earth Engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In May 2023, these natural disasters tragically claimed approximately 130 lives in the Northern and Western provinces of Rwanda, causing severe damage to road infrastructure and residential houses, particularly around the Mukungwa River. A study conducted by Prodromou (2023) demonstrated that landslides constitute a signi cant geohazard, causing human losses and signi cantly impacting the global economy. Leveraging Earth Observation and freely available Copernicus datasets, such as Sentinel-1 and Sentinel-2 satellite images, can assist in the systematic monitoring of landslides, overcoming limitations associated with in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In May 2023, these natural disasters tragically claimed approximately 130 lives in the Northern and Western provinces of Rwanda, causing severe damage to road infrastructure and residential houses, particularly around the Mukungwa River. A study conducted by Prodromou (2023) demonstrated that landslides constitute a signi cant geohazard, causing human losses and signi cantly impacting the global economy. Leveraging Earth Observation and freely available Copernicus datasets, such as Sentinel-1 and Sentinel-2 satellite images, can assist in the systematic monitoring of landslides, overcoming limitations associated with in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most widely remote sensing data sources for ground movements are satellite-based Synthetic Aperture Radar (SAR) and optical imagery, where various studies and techniques in different landscapes have emerged (Zhang et al, 2022;Alatza et al, 2020;Svigkas et al, 2016;Danezis et al, 2022). The combination of SAR and optical satellite data provides a more comprehensive understanding of the underlying processes since this integration detects both vertical and * Corresponding author horizontal displacements (Bacques et al, 2020;Prodromou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%